2024
DOI: 10.3390/ani14050728
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Food Intake on the Gut Microbiota of Endangered Père David’s Deer: Primary Evidence for Population Reintroduction

Qiying Mo,
Hongyu Yao,
Hong Wu
et al.

Abstract: Reintroduction has been successful in re-establishing several endangered wild animals in their historical habitats, including Père David’s deer (Elaphurus davidianus). Continuous monitoring of reintroduced individuals is essential for improving the sustainability of ex situ conservation efforts. Despite an increased recognition of the significance of the gut microbiome for animal health, the correlation between diet and the gut microbiome in E. davidianus is unclear. In this study, 15 fresh fecal samples of E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…These results can be explained principally by changes in the diet, which is considered the main factor that affects the GIT microbiota [17,70]. Mo et al [71] reported that the composition and diversity of the GIT microbiota are related to feed selection, indicating that the nutrients derived from edible plants may signi cantly in uence the relative abundance of gastrointestinal bacteria at the phylum and genus levels. Considering the differences in the results of the Bray-Curits and UniFrac distances, the overlaps in the PCoA plot showed some similarity in the evolutionary classi cation of faecal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be explained principally by changes in the diet, which is considered the main factor that affects the GIT microbiota [17,70]. Mo et al [71] reported that the composition and diversity of the GIT microbiota are related to feed selection, indicating that the nutrients derived from edible plants may signi cantly in uence the relative abundance of gastrointestinal bacteria at the phylum and genus levels. Considering the differences in the results of the Bray-Curits and UniFrac distances, the overlaps in the PCoA plot showed some similarity in the evolutionary classi cation of faecal microbiota.…”
Section: Discussionmentioning
confidence: 99%